Figures 1, 3, and 5 from Li Shihua, et al. - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2014)
Figures 1, 3, and 5 from Li S H, Xiao J T, Ni P, Zhang J, Wang H S, Wang J X. Monitoring paddy rice phenology using time series MODIS data over Jiangxi Province, China. Int J Agric & Biol Eng, 2014; 7(6): 28－36.